Water Pumping Using Solar Energy - Mehimmedetsi Boujemaa; Chenni Rachid (International Journal of Advances in Applied Sciences, 2017)
This article defines a simulation model of a simple system based essentially solar pumping of a photovoltaic generator and a DC motor with permanent magnet type of load as the centrifugal pump, in order to optimized the whole system it is necessary introduce a boost converter